Life and career of the violinist Virginia Sinay: an analysis of the great Sinay-Wolff tour of 1886 (Per Musi, 2021)
This article, developed through bibliographic and documental research, aims at establishing a biography, even though fragmented, of Virgínia Sinay, a violinist from Pará, a L. Massart’s student at the Paris Conservatory, and a prominent professor in her state. This research is based on an analysis of one of her biggest artistic ventures, namely the 1886’s tour, which was carried out with her sister and pianist Mathilde Sinay as well as with the famous Dutch violinist Johannes Wolff. Criticism on the concerts performed during the tour indicates the great technical and musical quality of the tree artists, it also highlights the excellent reception of the audience attending the concerts, and exhibits, in a clear fashion, some of the prejudices of that time, largely related to the concept of what it meant to be a woman and an artist in the nineteenth century.